Temporal dynamics of early visual word processing – Early versus late N1 sensitivity in children and adults. (October 2016) - Eberhard-Moscicka, Aleksandra K.; Jost, Lea B.; Fehlbaum, Lynn V.; Pfenninger, Simone E.; Maurer, Urs
Abstract: In the course of reading development children become familiar with letter strings and learn to distinguish between lexical and non-lexical items. In previous studies, the N1 component of the ERP was shown to reflect print tuning but also to be sensitive to lexical effects. It remains unclear, however, whether these two aspects of orthographic processing occur at the same time or in different time windows during the lengthy N1 component. Moreover, it is unclear whether these processes develop late or occur already at early stages of literacy acquisition and whether this is similar for native languages and languages acquired later in life. To address these questions, 27 children were tested longitudinally, i.e. before (mean: 7.6 years) and after one year of classroom-based English instruction. Additionally, 22 adult speakers of English as a foreign language (mean: 25.1 years) were investigated. A 128-channel EEG was recorded while participants performed a one-back task with native German words, English words, pseudowords and false-font strings. The event-related EEG analysis of early and late N1 phases revealed early effects related to print tuning and late effects related to lexical processing in the native, but not in the second language of adult readers. In the absence of lexicality effects in children, print tuning effects were found across both early and late N1 segments. The temporally distinct N1 sensitivities to print and lexicality reflect temporal dynamics of visual word processing, which seem to depend on reading expertise or maturation. Highlights: Effects of print tuning and lexicality were tested in visual word processing. Children and adults were assessed in the context of foreign language learning. Children's early and late N1 was sensitive to print tuning but not to lexicality. The adults' N1 indicated early print tuning and late lexicality effects. The late N1 lexicality effects in adults were found for L1 but not L2.